Epithelial Markers aSMA, Krt14, and Krt19 Unveil Elements of Murine Lacrimal Gland Morphogenesis and Maturation - Kuony, Alison; Michon, Frederic (Frontiers in Physiology, 2017)
As an element of the lacrimal apparatus, the lacrimal gland (LG) produces the aqueous part of the tear film, which protects the eye surface. Therefore, a defective LG can lead to serious eyesight impairment. Up to now, little is known about LG morphogenesis and subsequent maturation. In this study, we delineated elements of the cellular and molecular events involved in LG formation by using three epithelial markers, namely aSMA, Krt14, and Krt19. While aSMA marked a restricted epithelial population of the terminal end buds (TEBs) in the forming LG, Krt14 was found in the whole embryonic LG epithelial basal cell layer. Interestingly, Krt19 specifically labeled the presumptive ductal domain and subsequently, the luminal cell layer. By combining these markers, the Fucci reporter mouse strain and genetic fate mapping of the Krt14+ population, we demonstrated that LG epithelium expansion is fuelled by a patterned cell proliferation, and to a lesser extent by epithelial reorganization and possible mesenchymal-to-epithelial transition. We pointed out that this epithelial reorganization, which is associated with apoptosis, regulated the lumen formation. Finally, we showed that the inhibition of Notch signaling prevented the ductal identity from setting, and led to a LG covered by ectopic TEBs. Taken together our results bring a deeper understanding on LG morphogenesis, epithelial domain identity, and organ expansion.